Prevalence and duration of clinical symptoms of pediatric long COVID: findings from a one-year prospective study - Perestiuk, Vita; Kosovska, Tetyana; Volianska, Liubov; Boyarchuk, Oksana (Frontiers in Pediatrics, 2025)
BackgroundLong COVID in children remains a poorly understood condition with wide variability in clinical presentation, duration, and risk factors. The aim of this study was to assess the prevalence, spectrum, and duration of long COVID symptoms in pediatric patients following acute SARS-CoV-2 infection using a standardized follow-up tool.MethodsWe conducted a prospective cohort study involving 127 unvaccinated children aged 1 month to 18 years with long COVID according to the WHO definition and confirmed SARS-CoV-2 infection. Participants were followed up at 1–3, 3–6, 6–9, and 9–12 months post-infection using an adapted ISARIC Global Pediatric COVID-19 Follow-Up Questionnaire.ResultsPersistent symptoms of long COVID were reported in 85.8% of patients at 3 months, decreasing to 56.1% at 9 months and 32.5% at 12 months. The most common long-term symptoms included fatigue (52.0%), reduced physical activity (44.1%), and headache (35.3%). Multivariable logistic regression showed that older age was significantly associated with a higher risk of decreased physical activity (OR = 1.51, p = 0.038), lack of energy (OR = 2.00, p = 0.003), neurological symptoms (OR = 1.86, p = 0.007), headache (OR = 4.51, p = 0.000), memory impairment (OR = 5.12, p = 0.000), difficulty communicating (OR = 4.28, p = 0.000), difficulty concentrating (OR = 2.74, p = 0.001), cardiological symptoms (OR = 2.34, p = 0.022), sensory symptoms (OR = 2.66, p = 0.011), and dizziness (OR = 10.02, p = 0.034). Younger age was associated with insomnia (OR = 0.49, p = 0.018). Female sex was significantly associated with a greater likelihood of lack of energy (OR = 2.55, p = 0.048). Hospitalization status was only significantly associated with muscle pain, with outpatients more frequently affected (OR = 0.28, p = 0.029).Overall, 32.5% of all participants continued to experience symptoms of long COVID more than one year acute infection, with fatigue persisting in 19.8%, reduced physical activity in 13.9%, headache in 12.3%.ConclusionsLong COVID affects children across all age groups and may persist beyond one year in a significant subset. These findings highlight age- and sex-specific symptom profiles and underscore the need for structured pediatric follow-up.